Cell-type specific effects of mineralocorticoid receptor gene expression suggest intercellular communication regulating fibrosis in skeletal muscle disease - Gomatam, Chetan K.; Ingale, Pratham; Rodriguez, Gabriel; Munger, Sarah; Pomeranets, Rachel; Krishna, Swathy; Lowe, Jeovanna; Howard, Zachary M.; Rafael-Fortney, Jill A. (Frontiers in Physiology, 2024)
Introduction: Duchenne muscular dystrophy (DMD) is a fatal striated muscle degenerative disease. DMD is caused by loss of dystrophin protein, which results in sarcolemmal instability and cycles of myofiber degeneration and regeneration. Pathology is exacerbated by overactivation of infiltrating immune cells and fibroblasts, which leads to chronic inflammation and fibrosis. Mineralocorticoid receptors (MR), a type of nuclear steroid hormone receptors, are potential therapeutic targets for DMD. MR antagonists show clinical efficacy on DMD cardiomyopathy and preclinical efficacy on skeletal muscle in DMD models. Methods: We have previously generated myofiber and myeloid MR knockout mouse models to dissect cell-specific functions of MR within dystrophic muscles. Here, we compared skeletal muscle gene expression from both knockouts to further define cell-type specific signaling downstream from MR. Results: Myeloid MR knockout increased proinflammatory and profibrotic signaling, including numerous myofibroblast signature genes. Tenascin C was the most highly upregulated fibrotic gene in myeloid MR-knockout skeletal muscle and is a component of fibrosis in dystrophic skeletal muscle. Surprisingly, lysyl oxidase (Lox), canonically a collagen crosslinker, was increased in both MR knockouts, but did not localize to fibrotic regions of skeletal muscle. Lox localized within myofibers, including only a region of quadriceps muscles. Lysyl oxidase like 1 (Loxl1), another Lox family member, was increased only in myeloid MR knockout muscle and localized specifically to fibrotic regions. Discussion: This study suggests that MR signaling in the dystrophic muscle microenvironment involves communication between contributing cell types and modulates inflammatory and fibrotic pathways in muscle disease.